Wound debridement products and techniques: clinical examples and literature review - Nowak, Marcela; Mehrholz, Dorota; Barańska-Rybak, Wioletta; Nowicki, Roman (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2022)
The term “debridement” stands for the removal of necrotic material, scabs, devitalized tissues, dried serous fluid, infected tissues, biofilm, stratified epidermis, pus, hematomas, foreign bodies, bone fragments and other impurities whose presence delays wound healing. It is an inseparable element of wound healing therapy. Properly performed debridement leads to improvement of microcirculation in the wound, reduction in inflammation and lowering of the level of metalloproteinases, stimulation of wound edges and epidermis, reduction in unpleasant odour and reduction in the risk of infection and improvement of the patient’s quality of life. There are many debridement techniques approved by the European Wound Management Association. The selection of the most appropriate method depends on many factors such as tissue type, presence of biofilm, depth and location of the wound, underlying cause (venous, arterial), skills of the person performing the debridement and the preferences of the patient him/herself. In our work we present not only a systematic review of most of the debridement techniques used nowadays, but also our clinical cases showing results of those different techniques.